KDRT Ringan Harus Menjadi Delik Biasa: Analisis Yuridis dan Sosiologis UU PKDRT - Muhammad Rezfah Omar (Program Studi Hukum Universitas Pamulang, 2025)
Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT Law) classifies several domestic violence crimes, including minor ones, as complaint-based offenses as stipulated in Articles 51, 52, and 53. In practice, this classification often hinders the legal process due to the reliance on complaints from victims, who are often under pressure or threats, or due to the societal stigma that considers domestic violence a private matter. The Minister of Women's Empowerment and Child Protection (PPPA), Arifah Fauzi, stated in Press Release Number: B-257/SETMEN/HM.02.08/05/2025: